The Abundance of Bacteria Associated with Intertidal Seaweeds Sargassum sp. and Kappaphycus alvarezii in Ekas Bay - Muahiddah, Nuri; Cokrowati, Nunik; Affandi, Rangga Idris; Junaidi, Muhammad; Sumsanto, Muhammad; Dwiyanti, Septiana; Asri, Yuliana; Lumbessy, Salnida Yuniarti (Aquaculture Department, University of Mataram, 2024)
This study investigates the abundance and diversity of bacteria associated with two intertidal seaweeds, Sargassum sp. and Kappaphycus alvarezii, in Ekas Bay. Intertidal zones are dynamic environments where seaweeds and their associated microbial communities play crucial roles in ecological processes. Seaweeds host a variety of bacteria that contribute to nutrient cycling, seaweed health, and overall ecosystem function. The primary variable measured in this study was the bacterial abundance, expressed as Colony Forming Units per milliliter (CFU/mL). The conclusion of these findings has positive implications for the environmental health around the floating raft, base stakes, Sargassum sp. and Kappaphycus alverazii. The absence of harmful bacteria supports the sustainability of aquatic ecosystems and can provide positive benefits for the species inhabiting those areas.